The Analysis of Environmental Iinformation: A Study of the Dissemination, Mediation and Interpretation of News - Campbell, Fiona (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper discusses work recently completed for a doctoral qualification in the communication and information sciences. The underlying hypothesis of the research states that information changes as journalists gather, interpret and disseminate environmental information. The work includes a model which describes the flow of environmental information in the media and shows that. . .